Translingual Practices as Spatial Repertoires Employed by Interlocutors in Classroom Interaction - Risna Saswati; Setiono Sugiharto (Newinera Publisher, 2026)
The study investigates the transligual practices as spatial repertiores in classroom interaction. The method applied is a descriptive qualitative approach. It uses the classroom observation, interview and stimulated recall interview as the techniques of the data collection. The study employs the theories of sociocognitive affordances, translingual, classroom language use, and pragmatics. The outcomes reveal that the natural functions as the goals are achieved. The participants can shift the roles as the interlocutors who can apply the appropriate speech acts and the politeness strategies. The roles are changed and the study reveals the interaction is natural in which there is symmetrical relationship among the interlocutors in classroom interaction. It is as the results of the use of sosiocognitive affordances from the very beginning of the classroom interaction by the teachers and learners and continues to the end of the class. In the process, the roles of the teachers and learners gradually change into the interlocutors who have already the pragmatic competences to interact with other parties.